The Internet as means to increase the employees’ intercultural awareness - CAMARA, Assa (My University, 2020)
This study aimed to investigate how the employees’ can increase their intercultural awareness by using the internet to improve their intercultural communication skills in order to avoid misunderstanding during interaction with foreign customers. The ultimate goal of this research was to show how the internet helps the employees learn more about intercultural awareness. This research used a descriptive explanatory case study in which a questionnaire was given to the employees of the Exterior Bank of Algeria for the data collection. The results showed that employees’ intercultural communication competence improves due to the use of internet instead of a direct and face-to-face interaction with the customers. We assumed that the internet helps them learn and understand more about cultural differences that exist between their home culture and other foreign cultures. At the end of this research, we came out with the conclusion that interactivity and other abilities of internet have become influential aspects to improve employees’ knowledge of foreign cultures.
Case study: The employees of exterior Bank of Algeria CAPITALIZATION
Keywords: Culture; Intercultural awareness; Internet; Intercultural communication and competence; Globalization